Zarządzanie ryzykiem w instytucjach wykorzystujących muzułmańskie produkty finansowe - Katarzyna Czupa (Center for Social and Economic Research (CASE), 2016)
– Islamic finance is one of the most rapidly growing sectors in recent years. During the last decade the global value of Islamic assets has grown at yearly the pace of 10-12 per cent. Sharia compliant products, which are not based on the interest rate, has become popular also in non-Muslim countries, namely in the EU members states and in the US. Therefore, it is essential to address some practical aspects of use of these instruments such as risk management. The publication discusses characteristics of Islamic finance, financial risk that is included in main contracts and methods of its management (including practices of institutions that use Islamic financial products).
Keywords: G31; G21; 330; Financial sector; Other Regions; Islamic finance